Does Prior Abdominal Surgery Influence Technique Survival of Peritoneal Dialysis Patients? - Matos Silva, Rita (2024)
Introduction: Prior abdominal surgery may result in peritoneal membrane adhesions and fibrosis. Its impact on peritoneal membrane function and peritoneal dialysis technique survival has not been adequately investigated. The aim of our study was to investigate the effect of prior abdominal surgical procedures on peritoneal dialysis technique survival. Methods: We performed a retrospective, longitudinal study that included 155 peritoneal dialysis patients followed at our unit from September 2017 to September 2022. Two groups were created according to previous abdominal surgery status. The primary outcome was technique survival, defined as time to hemodialysis transition. Secondary outcomes were dialytic efficacy and risk of peritonitis. Results: Sixty‐eight patients (43.9%) had a previous history of abdominal surgery of whom 25 patients were found to have peritoneal adhesions at the time of catheter implantation. Prior abdominal surgical procedures or peritoneal adhesions did not impact technique survival (p‐value=0.498; p‐value=0.447, respectively). Although prior abdominal surgery did not increase the risk of peritonitis (OR 1.01; p‐value=0.988), patients with intra‐abdominal adhesions presented a trend for increased peritonitis risk during follow‐up (OR 2.324; p‐value=0.059), even after adjusting for patient’s comor‐ bidities and time in dialysis. Diabetes (HR 2.14; p‐value=0.027) and baseline Kt/V (HR 0.23; p‐value < 0.001) were the only variables with prognostic impact on technique survival in multivariate survival analysis. Conclusion: According to our results, prior abdominal surgical procedures do not appear to compromise technique survival in patients on peritoneal dialysis.